2006
DOI: 10.1161/01.str.0000226738.97426.6f
|View full text |Cite
|
Sign up to set email alerts
|

Blood Oxygen Level–Dependent MRI Allows Metabolic Description of Tissue at Risk in Acute Stroke Patients

Abstract: Background and Purpose-The delineation of the "penumbra" is of particular interest in acute stroke imaging. The "mismatch concept" applying perfusion-weighted imaging (PWI) and diffusion-weighted imaging (DWI) appears to be an oversimplification of the underlying electrophysiological tissue status. An additional parameter reflecting the metabolic state of the threatened brain tissue would improve our ability to describe the penumbra. One candidate is deoxyhemoglobin (deoxy-Hb) as an indicator of the oxygen ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 25 publications
8
107
1
1
Order By: Relevance
“…In contrast to previous studies, 15 we were able to detect significantly lower T2′ values within ADC lesions when compared with surrounding perfusion-restricted tissue (Figure 3), with an approximate decrease of 6%. Although this difference was numerically small, the finding was robust, attaining statistical significance for all TTP delays and TTP ranges under investigation.…”
Section: Differences Of T2′ Values Within Adc Lesions and Perfusion-rcontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies, 15 we were able to detect significantly lower T2′ values within ADC lesions when compared with surrounding perfusion-restricted tissue (Figure 3), with an approximate decrease of 6%. Although this difference was numerically small, the finding was robust, attaining statistical significance for all TTP delays and TTP ranges under investigation.…”
Section: Differences Of T2′ Values Within Adc Lesions and Perfusion-rcontrasting
confidence: 99%
“…15 Again, the T2′ reduction is best explained by an increase of deoxygenated haemoglobine because of an OEF increase within the area of impaired perfusion. A study correlating MRI-derived TTP abnormalities with PET-based OEF measurement demonstrated elevated OEF values, indicating a metabolic compensation in hypoperfused tissue.…”
Section: T2′ Values In Perfusion-restricted Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Before we are able to fit these components to the GESSE signal, T 2 decay must be allowed for in the model. Equations [3] and [4] are symmetric functions of t because magnetic field inhomogeneities around blood vessels are static. Conversely, due to the rapid fluctuation of spin-spin interaction, T 2 decay is an asymmetric function of t. The two mechanisms may therefore be fitted simultaneously without any risk of parameter coupling.…”
Section: ½4mentioning
confidence: 99%
“…Some researchers were able to provide a better estimation of the real penumbra with the changes in signal intensity from deoxyhemoglobin. 12 With the current understanding of the underlying mechanism of BOLD contrast, an absolute quantification of cerebral oxygenation is possible by measuring the signalintensity alteration induced by deoxyhemoglobin. On the basis of an analytic model, An and Lin 13 proposed some specifically designed sequences to obtain quantitative measures of the OEF; results consistent with those of PET studies were obtained in humans during both normocapnia and hypercapnia.…”
mentioning
confidence: 99%